Blender studio projects digital movie-making - Mullen, Tony, 1971- (Wiley Pub., 2010)
"Learn how to get professional results from Blender. Start from scratch-the way it happens in the studio-and create fully rendered objects with Blender open-source 3D animation software and this real-world, roll-up-your-sleeves guide. No time is wasted-this book plunges straight into step-by-step instruction designed to help you build skills and create solid assets for film, video, and games. Blender is gaining clout in professional settings, and you can get a running start with this series of hands-on tutorials that encompasses multiple disciplines. The book includes a DVD with starter, intermediate, and final files, as well as movie files to help you every step of the way. Helps you harness Blender, the free, open-source alternative to commercial CG packages such as Maya and 3ds Max. Presents projects that start from scratch and encompass multiple disciplines, thoroughly teaching you the Blender software. Shows you how to use Blender attributes and tools for professional results. Allows you to emerge with finished, renderable objects and assets for use in film, video, or games. Includes a DVD with starter, intermediate, and final files, plus movie files for reference. This unparalleled book contains everything you need to know to take your Blender skills to a new level"--